Facile infiltration of semiconducting polymer into mesoporous electrodes for hybrid solar cells - Abrusci, A; Ding, I; Al-Hashimi, M; Segal-Peretz, T; McGehee, MD; Heeney, M; Frey, G; Snaith, H (2011)
Hybrid composites of semiconducting polymers and metal oxides are promising combinations for solar cells. However, forming a well-controlled nanostructure with bicontinuous interpenetrating networks throughout the photoactive film is difficult to achieve. Pre-structured "mesoporous" metal oxide electrodes can act as a well-defined template for latter polymer infiltration. However, the long range infiltration of polymer chains into contorted porous channels has appeared to elude the scientific community, limiting the advancement of this technology. Here we present a structural and electronic characterisation of poly(3-hexylthiophene) (P3HT) infiltrated into mesoporous dye-sensitized TiO 2. Through a combination of techniques we achieve uniform pore filling of P3HT up to depths of over 4 μm, but the volumetric fraction of the pores filled with polymer is less than 24%. Despite this low pore-filling, exceptionally efficient charge collection is demonstrated, illustrating that pore filling is not the critical issue for mesoporous hybrid solar cells. © 2011 The Royal Society of Chemistry.